2020
DOI: 10.1016/j.scitotenv.2020.137675
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the NO2 distribution and relationship with traffic load in the Caribbean coastal city

Abstract: NO2 ambient concentrations were measured in a coastal Caribbean city. Barranquilla is a Caribbean city located in the North of Colombia that has approximately 1.200.000 inhabitants and possesses a warm, humid climate. In order to obtain the concentration of the contaminant in an adequate resolution, 137 passive diffusion tubes from Gradko© were installed. Diffusion passive tubes prepared with 20% TEA/water were located at the roadside between 1 and 5 m from the kerb edge. The sampling period was two weeks, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The effects of road traffic on air quality in large cities have been studied for years and the main pollutants emitted by vehicles are: particulate matter with a diameter lower than 10 μm (PM 10 ) ( Heydari et al, 2020 ; Ionescu et al, 2013 ; Pant and Harrison, 2013 ; Thorpe and Harrison, 2008 ), black carbon ( Ali et al, 2020 ; Invernizzi et al, 2011 ), CO 2 ( Zheng et al, 2020 ) and nitrogen dioxide (NO 2 ) ( Agudelo-Castañeda et al, 2020 ; Degrauewe et al, 2019 ). In the literature there are many works on the quantification and modelling of the dispersion of pollutants from their sources.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of road traffic on air quality in large cities have been studied for years and the main pollutants emitted by vehicles are: particulate matter with a diameter lower than 10 μm (PM 10 ) ( Heydari et al, 2020 ; Ionescu et al, 2013 ; Pant and Harrison, 2013 ; Thorpe and Harrison, 2008 ), black carbon ( Ali et al, 2020 ; Invernizzi et al, 2011 ), CO 2 ( Zheng et al, 2020 ) and nitrogen dioxide (NO 2 ) ( Agudelo-Castañeda et al, 2020 ; Degrauewe et al, 2019 ). In the literature there are many works on the quantification and modelling of the dispersion of pollutants from their sources.…”
Section: Introductionmentioning
confidence: 99%
“…The lockdowns of cities have been widely reported to bring significant positive impacts towards the environment, particularly on air quality, including sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ) and fine particles (PM 2.5 ) ( Filonchyk et al, 2020 ; Lancet Planet Health, 2020 ; Lau et al, 2020 ; Le Quere et al, 2020 ; Sarfraz et al, 2020 ; Tobias et al, 2020 ; Wang and Wang, 2020 ; Zhao et al, 2020 ). As the anthropogenic NO 2 is highly related to fossil fuel combustion from various transport modes, including vehicular traffic, marine shipping and commercial aircraft, the quarantine policies have resulted in a significant drop of NO 2 between late January and early March 2020 by 22.8 μg/m 3 in Wuhan alone and 12.9 μg/m 3 for the whole of China ( Agudelo-Castaneda et al, 2020 ; Herndon et al, 2004 ; Kaminska, 2019 ; Lancet Planet Health, 2020 ; Liu et al, 2020 ; Wang and Su, 2020 ). It was reported that transportation accounts for more than 50% of overall NOx (NO 2 + NO) in developed countries, while more than 23% in developing countries ( Crippa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the average is about 25% ( Chan et al, 2015 ; Li et al, 2017 ), and it is higher (up to 60%) in urban center and lower (down to 13%) in industrial zones. Being one of the designated criteria air pollutants, NO 2 has been widely reported to cause the formation of atmospheric particulates such as ammonia nitrate ( Agudelo-Castaneda et al, 2020 ). Consequently, NO 2 can lead to cardiovascular diseases such as hypertension, coronary heart disease and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Among the air pollutants with a declining trend, the rate of decrease in NO 2 was the lowest. Traffic emissions are the main contributor of NO x (NO + NO 2 ) ( Agudelo-Castaneda et al, 2020 ; Gao et al, 2021 ; Jin et al, 2021 ). Zhang et al (2019) pointed out certain control actions in the industrial sector that were effective from 2013 to 2017, such as strengthening industrial emission standards, upgrading industrial boilers, and ‘phasing out outdated industrial capacities’.…”
Section: Resultsmentioning
confidence: 99%